PENINGKATAN HASIL BELAJAR PENDIDIKAN PANCASILA MELALUI MODEL STAD DI SEKOLAH DASAR - Novandra Netanya; Taufik Hidayat; Iksam Iksam; Tri Wahyuningsih; Muhlis Muhlis (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The low level of active involvement and academic achievement of elementary school students in national education material due to the dominance of conventional learning patterns is the background of this research. This problem triggers students' failure to internalize the value of togetherness in a heterogeneous classroom. The focus of this research is to describe the implementation of the Student Teams Achievement Division (STAD) Cooperative Learning model in improving learning outcomes in Pancasila Education on the material of respecting the diversity of ethnicities and cultures of the nation. The steps of this Classroom Action Research (CLR) are carried out in two systematic cycles referring to the Kemmis and McTaggart model, including the stages of planning, action implementation, observation, and operational reflection. The research subjects include 28 students of grade IV A at SDN 019 Sungai Kunjang Samarinda with data collection via observation, tests, and documentation. Empirical quantitative data shows a surge in students' classical mastery from pre-cycle conditions of 46% (average 67.14), skyrocketing to 64.3% (average 72.68) in cycle I, and reaching a peak of optimal success of 79% (average 85.71) at the end of cycle II. The main conclusion confirms that the STAD model has proven to be very effective in boosting cognitive achievement while triggering an escalation of students' collaborative activity. Educators are recommended to adopt this group reward scheme as an alternative to improve the quality of basic instruction. ABSTRAK Rendahnya keterlibatan aktif serta capaian akademik siswa sekolah dasar pada materi kebangsaan akibat dominasi pola pembelajaran konvensional melatarbelakangi penelitian ini. Masalah tersebut memicu kegagalan siswa dalam menginternalisasi nilai kebersamaan di ruang kelas yang heterogen. Fokus penelitian ini adalah mendeskripsikan implementasi model Cooperative Learning tipe Student Teams Achievement Division (STAD) dalam meningkatkan hasil belajar Pendidikan Pancasila pada materi menghargai keragaman suku dan budaya bangsa. Langkah-langkah penelitian tindakan kelas (Classroom Action Research) ini dijalankan dalam dua siklus sistematis merujuk model Kemmis dan McTaggart, meliputi tahapan perencanaan, pelaksanaan tindakan, observasi, dan refleksi operasional. Subjek riset mencakup 28 peserta didik kelas IV A di SDN 019 Sungai Kunjang Samarinda dengan pengumpulan data via observasi, tes, dan dokumentasi. Data kuantitatif secara empiris menunjukkan lonjakan ketuntasan klasikal siswa dari kondisi pra-siklus sebesar 46% (rata-rata 67,14), meroket menjadi 64,3% (rata-rata 72,68) pada siklus I, dan mencapai puncak keberhasilan optimal senilai 79% (rata-rata 85,71) di akhir siklus II. Simpulan utama menegaskan bahwa model STAD terbukti sangat efektif mendongkrak pencapaian kognitif sekaligus memicu eskalasi keaktifan kolaboratif siswa. Pendidik direkomendasikan mengadopsi skema penghargaan kelompok ini sebagai alternatif perbaikan mutu instruksional dasariah.